Structural insights and functional implications of inter-individual variability in beta(2)-adrenergic receptor - Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Scientific Reports, 2016)
The human beta(2)-adrenergic receptor (beta(2)AR) belongs to the G protein-coupled receptor (GPCR) family and due to its central role in bronchodilation, is an important drug target. The inter-individual variability in beta(2)AR has been implicated in disease susceptibility and differential drug response. In this work, we identified nine potentially deleterious non-synonymous single nucleotide polymorphisms (nsSNPs) using a consensus approach. The deleterious nsSNPs were found to cluster near the ligand binding site and towards the G-protein binding site. To assess their molecular level effects, we built structural models of these receptors and performed atomistic molecular dynamics simulations. Most notably, in the Phe290Ser variant we observed the rotameric flip of Trp286(6.48), a putative activation switch that has not been reported in beta(2)AR thus far. In contrast, the variant Met82Lys was found to be the most detrimental to epinephrine binding. Additionally, a few of the nsSNPs were seen to cause perturbations to the lipid bilayer, while a few lead to differences at the G-protein coupling site. We are thus able to classify the variants as ranging from activating to damaging, prioritising them for experimental studies.

Loss of a water-mediated network results in reduced agonist affinity in a beta(2)-adrenergic receptor clinical variant - Nikte, V. Siddhanta; Sonar, Krushna; Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2021)
The beta(2)-adrenergic receptor (beta(2)AR) is a member of the G protein-coupled receptor (GPCR) family that is an important drug target for asthma and COPD. Clinical studies coupled with biochemical data have identified a critical receptor variant, Thr164Ile, to have a reduced response to agonist-based therapy, although the molecular mechanism underlying this seemingly ``non-deleterious'' substitution is not clear. Here, we couple molecular dynamics simulations with network analysis and free-energy calculations to identify the molecular determinants underlying the differential drug response. We are able to identify hydration sites in the transmembrane domain that are essential to maintain the integrity of the binding site but are absent in the variant. The loss of these hydration sites in the variant correlates with perturbations in the intra-protein interaction network and rearrangements in the orthosteric ligand binding site. In conjunction, we observe an altered binding and reduced free energy of a series of agonists, in line with experimental trends. Our work identifies a functional allosteric pathway connected by specific hydration sites in beta(2)AR that has not been reported before and provides insight into water-mediated networks in GPCRs in general. Overall, the work is one of the first step towards developing variant-specific potent and selective agonists.
Keywords: beta(2)-Adrenergic receptor; G protein coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

Water mediated allosteric network in beta 2AR T164I variant modulates agonist binding affinity - Nikte, Siddhanta V.; Sonar, Krushna; Tandale, Aditi; Sengupta, Durba; Joshi, Manali (European Biophysics Journal with Biophysics Letters, 2021)